2021
DOI: 10.3390/w13091279
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PVDF/Graphene Nanocomposite Membranes for Water Desalination with Enhanced Antifungal Activity

Abstract: Seawater desalination is a worldwide concern for the sustainable production of drinking water. In this regard, membrane distillation (MD) has shown the potential for effective brine treatment. However, the lack of appropriate MD membranes limits its industrial expansion since they experience fouling and wetting issues. Therefore, hydrophobic membranes are promising candidates to successfully deal with such phenomena that are typical for commercially available membranes. Here, several graphene/polyvinylidene (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Gontarek-Castro et al 148 used graphene nanosheets for fabricating PVDF/graphene nanocomposites and employed the nanocomposites in water desalination. They varied the amount of graphene nanosheets in the PVDF matrix and observed that the composites with 0.33 and 0.5 wt % of graphene nanosheets showed excellent water repellency.…”
Section: Application Of Pvdf-based Piezoelectric Materials In Energy ...mentioning
confidence: 99%
“…Gontarek-Castro et al 148 used graphene nanosheets for fabricating PVDF/graphene nanocomposites and employed the nanocomposites in water desalination. They varied the amount of graphene nanosheets in the PVDF matrix and observed that the composites with 0.33 and 0.5 wt % of graphene nanosheets showed excellent water repellency.…”
Section: Application Of Pvdf-based Piezoelectric Materials In Energy ...mentioning
confidence: 99%
“…Liu et al reported that GO dispersion displays the most effective inhibitory effect against E. coli cells by wrapping around bacterial cells more easily than agglomerated GO derivatives . Additionally, a recent study by Gontarek-Castro et al concluded that well dispersed graphene nanoplatelets (0.5 wt %) incorporated in a PVDF membrane matrix exhibit the highest fungal inhibition against Curvularia sp . Therefore, proper dispersibility of Gfam should be prioritized since it highlights Gfam’s dose-dependent effect.…”
Section: Discussionmentioning
confidence: 99%
“…72 Additionally, a recent study by Gontarek-Castro et al concluded that well dispersed graphene nanoplatelets (0.5 wt %) incorporated in a PVDF membrane matrix exhibit the highest fungal inhibition against Curvularia sp. 115 Therefore, proper dispersibility of Gfam should be prioritized since it highlights Gfam's dose-dependent effect.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In addition, some composite membranes filled with nanoparticles can be applied in other areas of separation, such as pervaporation, 60,61 water desalination 62 and water purification, 63 indicating that the formulation of the membrane composite is important for learning its practical value and application.…”
Section: Stability Of the Membranesmentioning
confidence: 99%